Effects of different stocking density and various phytogenic feed additives dosage levels on growing-finishing pigs - Hyun Ah Cho; Min Ho Song; Ji Hwan Lee; Han Jin Oh; Yong Ju Kim; Jae Woo An; Se Yeon Chang; Young Bin Go; Dong Cheol Song; Seung Yeol Cho; Dong Jun Kim; Mi Suk Kim; et al. (Journal of Animal Science and Technology, 2023)
This study was to investigate the effects of different phytogenic feed additives (PFA) dosage levels in growing- finishing pigs stressed by high stocking density. A total of 72 mix sexed 12 weeks growing pigs ([Landrace × Yorkshire] × Duroc) with initial body weight (BW) of 49.28 ± 4.58 kg were used for 8 weeks. There were 3 replicate pens in each treatment group, with 3 pigs per pen. The dietary treatment groups consisted of basal diets in animal welfare density (negative control [NC]), basal diet in high stocking density (positive control [PC]), PC + 0.04% essential oil (ES1), PC + 0.08% essential oil (ES2), PC + 0.10% bitter citrus extract & essential oil (CES1), PC + 0.20% bitter citrus extract & essential oil (CES2), PC + 0.05% grape pomace extract (GP1), PC + 0.10% grape pomace extract (GP2). The reduction of space allowance decreased (p < 0.05) average daily gain, feed efficiency, and digestibility of dry matter, crude protein, and gross energy. Also, the fecal score of PC groups increased (p < 0.05) compared with other groups. Basic behaviors (feed intake, standing, lying) were inactive (p < 0.05) and singularity behavior (biting) was increased (p < 0.10) under high stocking density. There was no difference in blood profile. However, the supplementation of PFA alleviated the negative effects such as reduced growth performance, nutrient digestibility, and some increasing stress indicators in th blood (cortisol) and animal behavior (biting). In conclusion, the negative effect of high stocking density was most effectively mitigated by the normal dosage of the mixture of bitter citrus extract and essential oil additive (CES1).